Različnost kot podjetniška priložnost: Slovenski podjetniški observatorij 2007/08 - Tominc, Polona; Močnik, Dijana; Duh, Mojca; Rus, Matej; Bradač Hojnik, Barbara; Crnogaj, Katja; Podgornik, Rok (University of Maribor Press, 2008)
Diversity as an Entrepreneurial Opportunity : Slovenian Entrepreneurship Observatory 2007/08. In the first part, we analysed the indicators of early-stage entrepreneurial activity of the population by statistical regions of Slovenia. Data were used from the Global Entrepreneurship Monitor for years 2004, 2005 and 2006. In the second part, we studied the impact of entrepreneurial dynamism (entries and exits) on economic growth in Slovenia. The third part deals with the basic characteristics of outsourcing among small and medium-sized enterprises in Slovenia. In the fourth part we studied the networking of Slovenian small and medium-sized enterprises. In the fifth part, we studied the developmental characteristics of Slovenian family enterprises and the support of their development efforts. Numerous studies, conducted mainly in countries with a tradition of family business, show that family businesses have many specific developmental features and it is accordingly necessary to create a support for their development efforts, namely support in the form of advisory services, education, forms of financing measures of economic policies and other forms of supportive environment. In the last part, we analysed the Slovenian companies in the year 2006.